2001
DOI: 10.1182/blood.v98.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver myelopoiesis occurs through distinct, prospectively isolatable progenitor subsets

Abstract: Hematopoietic fate maps in the developing mouse embryo remain imprecise. Definitive, adult-type hematopoiesis first appears in the fetal liver, then progresses to the spleen and bone marrow. Clonogenic common lymphoid progenitors and clonogenic common myeloid progenitors (CMPs) in adult mouse bone marrow that give rise to all lymphoid and myeloid lineages, respectively, have recently been identified. Here it is shown that myelopoiesis in the fetal liver similarly proceeds through a CMP equivalent. Fetal liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 75 publications
3
102
0
Order By: Relevance
“…In this experiment, we use the term "CLP-like" to define these cells phenotypically. We also identified a subset of early myeloid cells that were Lin Ϫ , sca-1 Ϫ , and c-kit ϩ ; these cells were further subdivided based on CD16 and CD34 expression into subsets corresponding to CMP, granulocyte-macrophage progenitors (GMP), and megakaryocyte-erythroid progenitors (MEP) (21). Because our experiments use the surface phenotype to define these subsets of cells, we use the operation terms GMP-like, CMP-like, and MEP-like.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, we use the term "CLP-like" to define these cells phenotypically. We also identified a subset of early myeloid cells that were Lin Ϫ , sca-1 Ϫ , and c-kit ϩ ; these cells were further subdivided based on CD16 and CD34 expression into subsets corresponding to CMP, granulocyte-macrophage progenitors (GMP), and megakaryocyte-erythroid progenitors (MEP) (21). Because our experiments use the surface phenotype to define these subsets of cells, we use the operation terms GMP-like, CMP-like, and MEP-like.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether the minor B cell progeny is derived from contaminants of lymphoid precursors among a high number of CMPs transplanted or whether putative bipotent B cell͞myeloid progenitors share their surface phenotype with CMPs. It shall be important to clarify this issue by future studies, because minor B cell potentials were observed similarly in both fetal and adult murine CMPs (2,26).…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by flow cytometric analysis of the different myeloid progenitor subsets. 27 Both common myeloid progenitors (CMPs; Fc␥R lo CD34 ϩ ) and granulocyte-monocyteprogenitors (GMPs; Fc␥R hi CD34 ϩ ) frequencies in Wnt3a Ϫ/Ϫ FLs were severely reduced. Megakaryocyte-erythrocyte progenitors (MEPs; Fc␥R lo CD34 Ϫ ) were not affected ( Figure 4F,G).…”
Section: Reduced Numbers Of Myeloid But Not B-lymphoid Progenitorsmentioning
confidence: 99%